Analisis masalah yang dihadapi pelaku UMKM di Kabupaten Klaten - Basuki, Basuki; Putri, Arie Rachma; Winoto, Agil Bayu; Oktavia, Amanda (Journal of Economics Research and Policy Studies, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in the economic development and growth of communities. This study aims to analyze the primary challenges faced by business operators in Klaten Regency across the aspects of production, marketing, and financing. The research employs a quantitative descriptive method, utilizing primary data collected from 30 business operators through questionnaires, interviews, focus group discussions, and observations. The majority of business operators are women, with an average age of 43 years, and they operate primarily in the culinary sector. The research findings indicate that the main challenges faced include limited marketing opportunities, restricted access to capital, and difficulties in obtaining adequate raw materials and production facilities. The implementation of digital marketing strategies remains minimal, hindering market expansion, and access to business financing is also limited. To address these issues, it is recommended to provide digital marketing training, ease access to microfinance, provide shared production facilities, and ensure the availability of raw materials. These efforts are expected to enhance the competitiveness and sustainability of SMEs in the face of the digital economy’s development and promote local economic growth.